Corticosteroids and risk of gastrointestinal bleeding in critically ill adults: Protocol for a systematic review. Issue 9 (24th May 2018) - Butler, E.; Møller, M. H.; Cook, O.; Granholm, A.; Penketh, J.; Rygård, S. L.; Aneman, A.; Perner, A.
Abstract : Background: Corticosteroids are frequently prescribed to critically ill patients. However, their use may increase the risk of gastrointestinal (GI) bleeding, which is associated with morbidity and mortality. Accordingly, we aim to assess whether continued administration of corticosteroids for >24 hours increases the rate of GI bleeding in adult critically ill patients compared to placebo or no treatment. Methods/Design: We will conduct a systematic review of randomized clinical trials with meta‐analysis and trial sequential analysis. The participants will be adult (as defined in the included trials) critically ill patients. The intervention will be any corticosteroid administered systematically for >24 hours and the comparator will be placebo or no treatment. The primary outcome will be rate of clinically important GI bleeding. We will systematically search EMBASE, MEDLINE, Medline In‐Process, Cochrane Library, Epistemonikos and trial registries for relevant literature, as well as perform a hand search. We will follow the recommendations by the Cochrane Collaboration and the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) statement. The risk of systematic errors (bias) and random errors will be assessed and the overall quality of evidence will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Discussion: The risk of GI bleeding in adult critically ill patients treated with corticosteroids is unknown. Hence, there is need for a robust systematic review to assess this risk and provide clinicians with a clearer understanding of the strength and limitations of existing data.